Evaluación de la crioconservación de ovocitos en conejos (Oryctolagus cuniculus) en el laboratorio de biotecnología de la reproducción de la carrera de medicina veterinaria de la Universidad Técnica de Cotopaxi - Cruz Negrete, Jorge Fernando (2015)
This research was conducted at the Reproductive Biotechnology laboratory Veterinary Medicine Career of Cotopaxi Technical University with the theme evaluation of oocytes cryopreservation in rabbits to determine if they are viable before and after cryopreservation. For the study Synthetic GnRH 0.2 ml was inoculated intramuscularly in 10 animals and after 2 hours they were sacrificed to collect the 20 ovaries. Getting ovaries were placed in to physiological saline to transport or shiping to the laboratory where a washing was performed by withdrawing annexed structures and utilizing the slicing technique which consists on fine ovaries cuts; follicular fluid was extracted in a Petri dish to observe at the stereomicroscope….